Totally crushed - Willard, Eliza (New York : Scholastic, 2007)
Annabel's life is turned upside down when she realizes the red Valentine's Day flower she received is from her friend, Sam.
"Candy apple"--Cover.
4.6
3-6
3-6
Bulletin (Center for Children's books)
Keywords: Valentine's Day -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Friendship -- Juvenile fiction; Valentine's Day -- Fiction; Dating (Social customs) -- Fiction; Friendship -- Fiction; Schools -- Fiction; Valentine's Day -- Fiction; Dating (Social customs) -- Fiction; Friendship -- Fiction; School stories